A security education Q&A. Issue 2 (3rd June 2014) - Veniamin Ginodman, Ms. Natalya Obelets, Mr Ram Herkanaidu, Mr; Kaspersky, Eugene; Furnell, Steven
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to highlight the importance of cyber security education as a means of enabling skilled professionals and ensuring adequate awareness amongst end users. Design/methodology/approach – The discussion examines the contribution made by the Kaspersky Academy student conference series, and then proceeds to consider some related questions posed to Eugene Kaspersky as the founder of the programme. Findings – The question and answer segment of the discussion identifies the ways in which academic qualifications and professional certifications can align to support a rounded security education for those aiming to become practitioners. Originality/value – The discussion provides a clear insight into the importance of security education and how it is being actively supported by one of the leading companies in the industry.